First rib fractures as indicators of serious intra and extra-thoracic injury in polytrauma and their impact on the morbidity and mortality - Al-Mourgi, Majed (International Surgery Journal, 2019)
Background: First-rib fractures are relatively rare compared with fractures of other ribs because of the broad structure deeply placed and protected location of the first rib. A high amount of energy is needed to cause a first-rib fracture; violent trauma, such as that involving motor vehicle accident, is a frequent cause of these fractures, as well as other serious intra-thoracic, head, cervical spine, and intra-abdominal injuries. First-rib fractures have traditionally been considered indicators of increased injury severity and mortality in major trauma patients. The aim was to study the significance of first-rib fractures as indicators of serious intra-thoracic and extra-thoracic injury in polytrauma and their impact on the morbidity and mortality in a high-altitude area in Al-Taif, Saudi Arabia. Methods: This is a retrospective study conducted in King Abdul-Aziz Specialist Hospital (KASH), Taif City, KSA. Patients with chest injuries who presented to the emergency department and were admitted to the hospital between November 2013 and March 2016 were included in the study. Data regarding first-rib fracture were collected, and the relationship between first-rib injuries and associated intra-thoracic and extra-thoracic injuries was analyzed. Results: There was a high incidence of first-rib fracture (23.45%), and 35.8% were bilateral. The most common associated chest injury was a pulmonary contusion (58.5%), followed by pneumothorax (32.1%), hemopneumothorax (20.7%), and surgical emphysema (20.7%). The most common associated extra-thoracic injuries in our study were skeletal injuries (47.4%), cervical spine injuries (11.3%), and head trauma (24.5%). Conclusions: Fractures of the first-rib are associated with serious thoracic and extra-thoracic injuries; they are associated only with increased morbidity in patients with polytrauma and have no independent impact on mortality.